2014
DOI: 10.14260/jemds/2014/2225
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intrathecal Ropivacaine With Dexmedetomidine for Operative and Post Operative Analgesia: A Prospective Randomized Study

Abstract: BACKGROUND: This prospective randomized double blind study was conducted to evaluate the effect and safety of intrathecal dexmedetomidine added to isobaric ropivacaine. MATERIALS AND METHODS: 120 adult female patients, who underwent vaginal hysterectomies, were randomly allocated to receive intrathecally either 3 ml of 0.75% isobaric ropivacaine + 0.5 ml normal saline (Group R) or 3 ml of 0.75% isobaric ropivacaine +5 μg dexmedetomidine in 0.5 ml of normal saline (Group D). Following intrathecal administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…Parmar NK et al, observed that in the group R time was 5.46±0.91 min, in the group D it was 5.54±0.85 min and the p value for difference was 0.60. 16 The time taken in the present study was longer compared to the study by Parmar NK et al 16 CONCLUSION…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Parmar NK et al, observed that in the group R time was 5.46±0.91 min, in the group D it was 5.54±0.85 min and the p value for difference was 0.60. 16 The time taken in the present study was longer compared to the study by Parmar NK et al 16 CONCLUSION…”
Section: Discussioncontrasting
confidence: 55%
“…Parmar NK et al, carried out a study among patients undergoing vaginal hysterectomy. 16 They added dexmedetomidine as an adjuvant to intrathecal ropivacaine. They also noted that in terms of peak sensory block level achieved, patients in the two groups were comparable.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also demonstrated that addition of dexmedetomidine or fentanyl to ropivacaine in spinal anaesthesia accelerated the sensory onset but has no effect on motor block onset. 10,13,16,21 Duration of motor block was significantly longer in Group RD (360.14±16.52 min) as compared to Group R (284.43±16.57min). Duration of motor block was comparable in group R and group RF.…”
Section: Observations and Resultsmentioning
confidence: 88%
“…[8][9][10][11][12] However there is scarcity of data in which ropivacaine has been used in SAB for vaginal hysterectomy in which there is more extensive surgery, needing more relaxation than above mentioned surgeries. 13 This prompted us to plan present study. Local anaesthetic when used alone is associated with short duration of action.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation